1986
DOI: 10.1017/s1742758400003027
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tsetse attractants from excretory products of a wild host animal, Syncerus caffer

Abstract: Urine from the buffalo, Syncerus coffer, a natural host of the tsetse, has been shown previously to be a potent olfactory attractant for tsetse in the field. The attractant compounds have been found to be extractable into dichloromethane. Fractionation of the extracts by liquid flash chromatography yielded four fractions one of which gave a seven-fold increase in trap catches in the field compared to the control traps. Gas chromatographic and gas chromatography-mass spectrometric analysis of this fraction reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 5 publications
(6 reference statements)
1
65
1
Order By: Relevance
“…chicken coops and animal stalls. Attractants for tsetsē ies have already been identi®ed in vertebrate urine (Hassanali et al 1986;Owaga et al 1988;Saini 1990).…”
Section: Signi®cance Of Ammonia For Triatominesmentioning
confidence: 99%
“…chicken coops and animal stalls. Attractants for tsetsē ies have already been identi®ed in vertebrate urine (Hassanali et al 1986;Owaga et al 1988;Saini 1990).…”
Section: Signi®cance Of Ammonia For Triatominesmentioning
confidence: 99%
“…Acetone, l-octen-3-ol (octenol) and carbon dioxide from bovine breath and phenols from urine are potent olfactory attractants for several species of the morsitans group of tsetse (Vale & Hall, 1985;Hassanali et al, 1986;Bursell et al, 1988) and some of these chemicals are now being used as baits with * Address for correspondence: Tsetse Unit, Mbita Point Field Station, ICIPE, PO Box 30, Mbita Point, Homa Bay, Kenya. Fax: 254 385 2290 insecticide-coated targets or untreated traps to control tsetse Dransfield et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several workers have demonstrated the behavioural significance of chemical compounds as a source of attractants for anthropophilic mosquitoes (Cork, 1996;Cork & Park, 1996;Geier et al, 1996;Knols et al, 1997;Takken et al, 1997). The olfactory stimuli implicated in host location by haematophagous insects to date include carbon dioxide, lactic acid, acetone, butanone, 1-octen-3-ol (henceforth referred to as octenol), phenolic components of urine (Hassanali et al, 1986;Bursell et al, 1988) and short-chain carboxylic acids .…”
Section: Introductionmentioning
confidence: 99%
“…Octenol and acetone, which were first identified as host attractants for tsetse flies (Hall et al, 1984;Hassanali et al, 1986), have been shown to attract certain mosquito species in the field. The established role of octenol as a kairomone for many mosquito species has been well documented (Kline, 1994).…”
Section: Introductionmentioning
confidence: 99%